Biochar utilisation in the anaerobic digestion of food waste for the creation of a circular economy via biogas upgrading and digestate treatment. (August 2021) - Lee, Jonathan T.E.; Ok, Yong Sik; Song, Shuang; Dissanayake, Pavani Dulanja; Tian, Hailin; Tio, Zhi Kai; Cui, Ruofan; Lim, Ee Yang; Jong, Mui-Choo; Hoy, Sherilyn H.; Lum, Tiffany Q.H.; Tsui, To-Hung; et al.
Graphical abstract: Highlights: Wood waste-derived biochar was used first for upgrading biogas from food waste. The biochar was next applied to treat the food waste anaerobic digestate. The mixture of biochar and AD solids were utilised to grow kale, lettuce and rocket. Virgin raw biochar was not effective at absorbing carbon dioxide. Biochar was efficacious for wastewater treatment and biofertiliser application. Abstract: A wood waste-derived biochar was applied to food-waste anaerobic digestion to evaluate the feasibility of its utilisation to create a circular economy. This biochar was first purposed for the upgrading of the biogas from the said anaerobic digestion, before treating and recovering the nutrients in the solid fraction of the digestate, which was finally employed as a biofertilizer for the organic cultivation of three green leafy vegetables: kale, lettuce and rocket salad. Whilst the amount of CO2 the biochar could absorb from the biogas was low (11.17 mg g −1 ), it could potentially be increased by modifying through physical and chemical methods. Virgin as well as CO2 -laden biochar were able to remove around 31% of chemical oxygen demand, 8% of the ammonia and almost 90% of the total suspended solids from the digestate wastewater, which was better than a dewatering process via centrifugation but worse than the industry standard of a polytetrafluoroethylene membrane bioreactor. Nutrients were recovered in the solid fraction of the digestate residue filtered by the biochar, and utilised as a biofertilizer that performed similarly to a commercial complete fertilizer in terms of aerial fresh weight growth for all three vegetables cultivated. Contingent on the optimal upgrading of biogas, the concept of a circular economy based on biochar and anaerobic digestion appears to be feasible.